FINANCIAL SUPPLY OF SOCIO-ECONOMIC DEVELOPMENT OF TERRITORIAL COMMUNITIES IN DECENTRALIZATION CONDITIONS - Shchur , R. I.; Kokhan , I. V. (The actual problems of regional economy development, 2018)
The article considers conceptual implications of financial provision of socio-economic development of communities in the condition of decentralization. The dynamics of revenues is analyzed of united territorial communities in Ukraine in 2015-2017. The main financial tools are investigated of stimulation of socio-economic development of territorial communities in Ukraine.